2018
DOI: 10.3389/fneur.2018.00055
|View full text |Cite
|
Sign up to set email alerts
|

Severe Blood–Brain Barrier Disruption in Cardioembolic Stroke

Abstract: BackgroundPrevious studies demonstrated that cardioembolism (CE) was prone to develop hemorrhagic transformation (HT), whereas hyper-permeability of blood–brain barrier (BBB) might be one reason for the development of HT. We, thus, aimed to investigate whether the BBB permeability (BBBP) was higher in CE stroke than other stroke subtypes in acute ischemic stroke (AIS) patients.MethodsThis study was a retrospective review of prospectively collected clinical and imaging database of AIS patients who underwent CT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…Second, in the acute phase of cerebral infarction, the extent of brain injury and bloodbrain barrier (BBB) disruption may determine the degree of acute-phase inflammatory response. It has been confirmed that the degree of BBB destruction in CES patients is more serious than that in patients with other stroke subtypes (28), and this could be related to CRP levels (29). While these mechanisms may play a role in the increased CRP we observed, two studies have reported no differences in CRP levels among stroke subtypes (30,31).…”
Section: Discussionsupporting
confidence: 63%
“…Second, in the acute phase of cerebral infarction, the extent of brain injury and bloodbrain barrier (BBB) disruption may determine the degree of acute-phase inflammatory response. It has been confirmed that the degree of BBB destruction in CES patients is more serious than that in patients with other stroke subtypes (28), and this could be related to CRP levels (29). While these mechanisms may play a role in the increased CRP we observed, two studies have reported no differences in CRP levels among stroke subtypes (30,31).…”
Section: Discussionsupporting
confidence: 63%
“…According to the literature, permeability maps, as the primary imaging assessment tool to evaluate HT, may underestimate permeability measurements [8, 9]. In addition, in some patients, reconstruction of these maps may not be possible due to the abnormal contrast curves caused by insufficient scan time [10, 11]. Recently, CT-based quantitative NWU has been described as an important imaging biomarker of malignant edema and lesion age in patients with AIS [12, 14].…”
Section: Discussionmentioning
confidence: 99%
“…In areas of low blood flow, contrast delivery is severely limited, and permeability measurements will be artificially reduced [8, 9]. In addition, the acquisition time for permeability imaging is long (at least 50–60 s), and 10–25% of patients are excluded because of motion artifacts or abnormal venous output function curves, resulting in failed reconstruction [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…It involves using the Patlek method to calculate microvascular permeability metrics, transendothelial transfer constant (kPS) or permeability surface area product (PS, ml/min/100 g), based on time-density curves for each pixel ( 19 , 21 ). The use of relative permeability-surface area product (rPS = PS/CBF × 100) is of interest due to the correction for the potential influence of cerebral blood flow ( 19 , 20 , 67 ). In normal parenchyma, the permeability product is null for large molecules, such as iodine contrast.…”
Section: Tissue-based Propertiesmentioning
confidence: 99%